2019
DOI: 10.1016/j.fuel.2019.03.121
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of particle radiation and its effect on NO prediction in a pilot-scale facility for both air and oxy-coal combustion

Abstract: Radiation heat transfer plays an important role in pulverised coal combustion, influencing the overall combustion efficiency, pollutant formation and flame ignition and propagation. In this paper, the radiation properties of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In addition, their simulations showed that RHT is the dominant mode of heat transfer in these flames and radiation from the participating gases contributes for 75% of the total RHT. Huyun et al [245] modelled a 250 kW pilot scale combustion test facility (CTF) by using FLUENT. Simulations considered, on the one hand, a reference radiative model involving the non-grey WSGG coupled to Planck-mean radiative properties for the particles derived from Mie theory and, on the other hand, simplified radiative models based on grey formulations of the WSGG and simple constant or linear radiative properties for the particles.…”
Section: Coal Combustionmentioning
confidence: 99%
“…In addition, their simulations showed that RHT is the dominant mode of heat transfer in these flames and radiation from the participating gases contributes for 75% of the total RHT. Huyun et al [245] modelled a 250 kW pilot scale combustion test facility (CTF) by using FLUENT. Simulations considered, on the one hand, a reference radiative model involving the non-grey WSGG coupled to Planck-mean radiative properties for the particles derived from Mie theory and, on the other hand, simplified radiative models based on grey formulations of the WSGG and simple constant or linear radiative properties for the particles.…”
Section: Coal Combustionmentioning
confidence: 99%
“…Syngas produced from the gasifier is further burned in the oxy-fuel combustion chamber for power generation, and the flue gas emitted is processed for CO2 capturing by cooling. A numerical investigation on radiation and gas property of the particles in order to predict the formation of NOx pollutants in pulverised coal was carried out (Huynh et al, 2019). Furthermore, gasification process offers more scope for recovering products from waste than incineration.…”
Section: Introductionmentioning
confidence: 99%
“…The combustion energy enters the thermodynamic cycle through the boiler to generate power; thus, there is considerable focus on improving the energy conversion efficiency of combustion. On the one hand, radiation represents a large proportion of the combustion system; thus, the effective utilization of radiative energy is of great significance for energy conversion. On the other hand, the optimization and restructuring of the thermodynamic cycle system provide a theoretical basis for efficient energy conversion.…”
Section: Introductionmentioning
confidence: 99%